Circular economy strategies to reduce plastic pollution in the textile industry: a systematic literature review - Perez Burgos, Cesar Del Piero; Silva Pinta, Adriana Belen (LACCEI, 2025)
The textile industry generates a large amount of synthetic plastic waste, which represents an increasingly significant environmental challenge. This systematic literature review explored the circular economy strategies implemented between 2020 and 2025 to reincorporate this waste into the textile supply chain. The search was conducted using the PICOC model in academic databases such as Scopus and Web of Science, allowing for the selection of 37 studies aligned with specific criteria. The analysis was organized around five axes: type of waste, reintegration technologies, comparison with linear models, supply chain efficiency, and integration mechanisms. A transition toward circular models was identified that employ technologies such as mechanical and chemical recycling, blockchain, digital traceability, and design for disassembly. These practices allow the reincorporation of materials such as polyester, nylon, and acrylics into production processes, reducing dependence on virgin polymers and improving operational efficiency. Despite progress, technical, economic, and regulatory challenges persist that hinder wider adoption. The circular approach is presented as an effective way to transform the textile sector, provided it is accompanied by technological innovation, appropriate regulatory frameworks, and collaboration between the various actors in the chain. Keywords: circular economy, textile waste, textile industry, recycling, innovation.